2014
DOI: 10.4028/www.scientific.net/amm.698.283
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Transition Zone Structure in Welded Joints between Dissimilar Steels

Abstract: The results of structural research of welded joints between pearlitic high-carbon steel and austenitic chrome-nickel steel obtained by contact welding are presented. As a result of the diffusion process and mechanical mixing of steels local alloyed areas surrounded by pearlitic colonies of high-carbon steel are formed in the transition zone of the weld. The transmission electron microscopy (TEM) has been employed. The formation of the austenitic-martensitic microstructure occurs due to reducing the amount of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…According to the structural investigation results welds with inserts and without them were characterized by clear-distinguished boundaries between a weld joint and the base material as well as local zones in carbon steel and the martensitic interlayer in chromium-nickel steel. The results obtained were in good agreement with previously obtained results of initial joint investigations without low-carbon inserts [12,16]. However a width of these zones in joints with a barrier layer was significantly less (Fig.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…According to the structural investigation results welds with inserts and without them were characterized by clear-distinguished boundaries between a weld joint and the base material as well as local zones in carbon steel and the martensitic interlayer in chromium-nickel steel. The results obtained were in good agreement with previously obtained results of initial joint investigations without low-carbon inserts [12,16]. However a width of these zones in joints with a barrier layer was significantly less (Fig.…”
Section: Resultssupporting
confidence: 92%
“…Hadfield steel needs fast cooling while carbon steel should be cooled at a medium speed. Previous investigations [11][12][13][14] showed that high-strength martensitic structures could appear between carbon (rail) steel and chromium-nickel steel in welds. To avoid the formation of such structures a longtime heat treatment (annealing at 1000 °C during 3-5 hours) was suggested in [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the precipitation of carbide particles on the grain boundaries has pinning effects on the grain growth [ 54 , 55 , 56 ]. Therefore, the precipitated carbides in the TZ work as obstacles for the movement of the grain boundaries, which hinders the coarsening of the grains size at the TZ and works as heterogeneous nucleation sites, which enhances the formation of fine equiaxed structures in the TZ; therefore, the size of the grains at the TZ was finer than the grains which exist at the FB and CGHAZ, which is similar to the results presented in the literature [ 52 , 57 , 58 ].…”
Section: Discussionsupporting
confidence: 85%